COMPARISON OF PROFILES, ANTIOXIDANT, ENZYME INHIBITORY AND CYTOTOXIC CAPACITIES OF PHENOLIC EXTRACTS OF FIVE Teucrium SPECIES FROM TURKIYE - Ozturk Urek, Raziye; Tarhan, Leman; Ayyildiz, Yildizay; Nakiboglu, Mahmure (Journal of the Chilean Chemical Society, 2025)
The study aims to investigate the phenolic compounds, antioxidant-enzyme inhibitory activities, and cytotoxic effects of the flavonoid subgroups and phenolic acid extracts of the Teucrium chamaedrys ssp chamaedrys (TCC), T. chamaedrys ssp lydium (TCL), T. polium (TP), endemic T. alyssifolium (TA), T. kotschyanum (TK) from Türkiye. Among the phenolics determined, phenolic acids were found to be in the highest concentration, particularly caffeic, p-coumaric, and t-cinnamic acids. In term of antioxidant activity, the best IC50 values of 1,1-diphenyl-2-picrylhydrazyl (23.21±0.78 µg/mL), hydroxyl (HO•) (1.01±0.01 µg/mL), nitric oxide scavenging (12.28±0.91 µg/mL) and metal chelating (20.10±0.66 µg/mL) were determined in TP, TCL, TK, and TA, respectively. Additionally, TCL has a 5.05-times higher quenching capacity of HO• compared to butylated-hydroxytoluene. The best acetylcholinesterase and tyrosinase inhibitions were detected in TK and TCC, respectively. While the cytotoxic properties of these extracts against HepG2, OE-33, HeLa, ACC-201, and MCF-7 cancer cells were detected, more extensive effect was observed against HepG2 in TCC, TP, TA, and TCL. According to the results, the richness of Teucrium species in phenolic compounds, the importance of their antioxidant-enzyme inhibitory properties and their cytotoxic effects make their potential as natural component sources in food and medical come to the fore.